Current status of carbapenemases in Latin America. Issue 7 (July 2013) - Maya, Juan J; Ruiz, Sory J; Blanco, Victor M; Gotuzzo, Eduardo; Guzman-Blanco, Manuel; Labarca, Jaime; Salles, Mauro; Quinn, John P; Villegas, Maria V
Enterobacteriaceae and non fermenting Gram-negative bacilli have become a threat to public health, in part due to their resistance to multiple antibiotic classes, which ultimately have led to an increase in morbidity and mortality. β-lactams are currently the mainstay for combating infections caused by these microorganisms, and β-lactamases are the major mechanism of resistance to this class of antibiotics. Within the β-lactamases, carbapenemases pose one of the gravest threats, as they compromise one of our most potent lines of defense, the carbapenems. Carbapenemases are being continuously identified worldwide; and in Latin America, numerous members of these enzymes have been reported. In this region, the high incidence of reports implies that carbapenemases have become a menace and that they are an issue that must be carefully studied and analyzed.